Design and Analysis of Brushless Doubly Fed Induction Generator. (2015) - Resmi R.,; Agoram, C. Arun; Adithya, P.; Vanitha, V.
Abstract: Brushless Doubly Fed Induction Generator (BDFIG) is one of the upcoming machines which is under research study to be used in offshore windfarms as it has many advantages over the conventional machines. Electromagnetism, the study of electric and magnetic fields plays the vital role in the design of machines. Electric machines are used in novel applications around the world, driven by the need for greater power efficiency in the transportation, aerospace and defense, and industrial automation areas. It is difficult to design a machine to meet all the performance criteria. ANSYS Maxwell software is a powerful tool to analyze all the relevant performance indices related to machine design. Finite element method is used in this software for the accurate analysis of the modeled machine. In this paper, design of 1.1 kW Brushless Doubly Fed Induction Generator (BDFIG) for 2/6 pole configuration and 4/8 pole configuration are done and analysis of the configurations are carried out using ANSYS Maxwell software.